2016
DOI: 10.1016/j.pmrj.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Efficacy of Particulate Versus Nonparticulate Corticosteroids in Epidural Injections

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 57 publications
0
26
1
1
Order By: Relevance
“…Regarding particulate vs nonparticulate steroids, a recent systematic review has found no evidence of a significant difference in efficacy. On the basis of potential catastrophic complications with particulate steroids, nonparticulate steroids are recommended [89].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding particulate vs nonparticulate steroids, a recent systematic review has found no evidence of a significant difference in efficacy. On the basis of potential catastrophic complications with particulate steroids, nonparticulate steroids are recommended [89].…”
Section: Resultsmentioning
confidence: 99%
“…But these adverse effects occurred mainly in cases in which particulate steroid was administered, and its replacement with a non-particulate steroid could reduce serious side effects (50)(51)(52)(53). A Soluble non-particulate steroid reportedly showed comparable and non-inferior clinical outcomes to those of particulate steroid (50,54,55). Thus injection of soluble nonparticulate steroid could reduce the fear or concerns of serious side effects and consequently prevent unnecessary avoidance of TFEI (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently limited evidence to support particulate vs. nonparticulate steroids for epidural injections in improving pain or function in the nononcologic population. 18 It is notable that the practitioner should be cautious when using particulate steroids, especially for TFESI, given the increased risk of spinal ischemia and in the case of cervical ESI, an added potential risk of posterior circulation infarction due to embolization. 19 A couple proposed mechanisms of spinal cord infarction involve direct injury to or embolization of particulate steroids through the artery of Adamkiewicz or other radiculomedullary arteries in the intervertebral foramen.…”
Section: Discussionmentioning
confidence: 99%
“…19 A couple proposed mechanisms of spinal cord infarction involve direct injury to or embolization of particulate steroids through the artery of Adamkiewicz or other radiculomedullary arteries in the intervertebral foramen. 18 This adverse effect may be pronounced in the oncologic population, in which ESI may be performed close to neovascularized tissue. Nevertheless, no patients in this study suffered from such complications.…”
Section: Discussionmentioning
confidence: 99%